NME/NM23/NDPK and Histidine Phosphorylation - Adam, Kevin (Int J Mol Sci, 2020)
The NME (Non-metastatic) family members, also known as NDPKs (nucleoside diphosphate kinases), were originally identified and studied for their nucleoside diphosphate kinase activities. This family of kinases is extremely well conserved through evolution, being found in prokaryotes and eukaryotes, but also diverges enough to create a range of complexity, with homologous members having distinct functions in cells. In addition to nucleoside diphosphate kinase activity, some family members are reported to possess protein-histidine kinase activity, which, because of the lability of phosphohistidine, has been difficult to study due to the experimental challenges and lack of molecular tools. However, over the past few years, new methods to investigate this unstable modification and histidine kinase activity have been reported and scientific interest in this area is growing rapidly. This review presents a global overview of our current knowledge of the NME family and histidine phosphorylation, highlighting the underappreciated protein-histidine kinase activity of NME family members, specifically in human cells. In parallel, information about the structural and functional aspects of the NME family, and the knowns and unknowns of histidine kinase involvement in cell signaling are summarized.